The teaching of physics through scientific experiences with recyclable and low cost materials (Research, Society and Development, 2019)
This work presents a project of scientific experiments with materials found on a daily basis, developed with high school students of the morning, afternoon and evening shifts, in EEEFM Manoel Lobato, located in the municipality of Primavera / PA. The aim of the project was to reduce the school dropout rate and stimulate the study of the mathematical, physical and chemical disciplines, since they are areas that have great difficulty in learning the contents. The activities focused on the research and production of scientific experiments with recyclable or low cost materials, portraying contents seen in the classroom and a different context, with different applications. The students were instructed by the teacher in each suggested experimental activity, highlighting important information for each step required to construct the experiment. As a result of the activities, it was highlighted the commitment and motivation demonstrated by the students involved, as well as the search for scientific rigor and interest in carrying out similar activities in the following year.